Decoding Text, Shaping Data: A Digital Study of the Keywords Walandi and Pakêmpalan in Kadjawen magazine 1927–1931 - Suryani, Sri (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2025)
This study presents a linguistic analysis and an examination of political discourse in the Javanese-language magazine Kadjawen, published during the Dutch colonial period from 1927 to 1931. This study is exploratory in nature and has been elaborated using a Digital Humanities approach, with an emphasis on a conceptual orientation towards discourse analysis related to the relationship between language, power, and colonialism. This study also applies digital text analysis methods, such as frequency and concordance analysis, with a primary focus on investigating the occurrence and contextual proximity of two keywords: Walandi “Dutch” and pakêmpalan “association” or “organisation”, which are scattered throughout the text corpus. The data was taken from the freely accessible digital edition of Kadjawen on the website sastra.org. There were a total of 201 texts as raw data, which were then converted to plain text format and analysed using Python and Voyant Tools. The results of the analysis show that despite being subject to colonial restrictions and rules, Kadjawen displayed linguistic strategies that reflected the negotiation between Javanese cultural identity and Dutch colonial power, as well as its involvement in the national discourse that developed in the late 1920s. === Penelitian ini memaparkan kajian wacana linguistik dan diskursus politik di dalam majalah berbahasa Jawa Kadjawen yang terbit pada masa kolonial Belanda, dari periode 1927 hingga 1931. Penelitian bersifat eksploratif dan telah dielaborasikan dengan pendekatan humaniora digital, menekankan orientasi konseptual terhadap kajian wacana terkait relasi antara Bahasa, kekuasaan, dan kolonialitas. Selanjutnya, penelitian menerapkan metode analisis teks digital, khususnya analisis frekuensi dan konkordansi, dengan fokus utama melakukan penelusuran atas kemunculan serta kedekatan kontekstual dua kata kunci, yaitu Walandi “Belanda” dan Pakêmpalan “perkumpulan” atau “organisasi”, yang tersebar di dalam korpus teks. Data diambil dari edisi digital Kadjawen yang bebas akses di situs sastra.org. Terdapat total 201 teks sebagai data mentah yang kemudian dikonversi ke format plain teks, kemudian dianalisis menggunakan Python serta Voyant Tools. Hasil penelitian menunjukkan bahwa meski berada di dalam batasan serta aturan kolonial, Kadjawen menampilkan strategi kebahasaan yang merefleksikan adanya negosiasi antara identitas kultural Jawa dengan kekuasaan kolonial Belanda serta keterlibatannya terhadap wacana kebangsaan yang berkembang pada akhir 1920-an.